Penguatan Sumber Daya Manusia melalui Pemanfaatan Aplikasi Android Edukatif di Era Digital - Bertha Meyke Waty Hutajulu; Caka Gatot Priambodo; Halimatus Sa’diah; Vici Febriana; Irnawati Irnawati (PASAI : Jurnal Pengabdian kepada Masyarakat, 2026)
This community service initiative aimed to introduce and implement an Android-based application for recognizing world national flags as an interactive learning tool for the public, particularly students. The activity employed a participatory training approach that combined an introduction to the application, hands-on practice, and an evaluation using a flag recognition test. The results indicate that using the Android application enhanced participants' knowledge of world flags and national identities while fostering an interest in learning and engagement with digital media. Furthermore, the activity improved digital literacy by demonstrating how mobile applications can be utilized for educational purposes. Despite limitations regarding devices and internet connectivity, the application proved to be practical and engaging, with the potential for further development as a sustainable learning tool within the community.